Déminéralisation des eaux de forage de la région d’Ouled Abbès et son impact sur l'environnement (Souk Ahras, extrême Nord-Est Algérien ) - Antri Fafa; Soualeh Oussama (My University, 2022)
The principal objective of this work is to determine the quality of treated water and to evaluate the performance of the demineralization station of the drilling water, which supplies the town of Sidi-Fredj, by reverse osmosis. The study was carried out by taking water samples at five points in the treatment chain. The monitoring of certain physico-chemical parameters (pH, electrical conductivity of water, TH, TAC and concentrations of ions (The principal objective of this work is to determine the qualiy of treated water and to demineralization station of the drilling water, which supplies the town of Sidi-Fredj, by reverse osm evaluate the performance of th The study was carried out by taking water samples at five point s in the treatment chain. The monitoring of certain physico-chemical parameters (pH, electric conductivity of water, TH TAC and concentrations of ions ( NO ᶟ - , PO4ᶟ - , Ca ² + , Mg ²+ , C L - , and SO 4- ) showed that leaving the water treatment plant is of very good quality by comparing the values measured for each parameter with the standards of potability. The other aspect that concerns this study is the potential impact of liquid discharges responsible for these station mainly wadis who receive and the environment in general. -------------------------------------------------------------------------------------------------------------------------------------------------------------- الهدف الرئيسي من هذا العمل هو تحديد نوعية الماء لمعالج و تقدير مدى فعالية محطة تحلية المياه الجوفية التي تزود سكان بلدية سدي فرج عن طريق التناضح العكسي تمت هذه الدراسة عند اخذ عينات مائية عند خمس مراحل مختلفة للمعالجة على مستوى المحطة. متابعة تغير بعض العناصر الفيزيائية والكيميائية للمياه (الأس الهيدروجيني التوصيل الكهربائي للمياه، pH و تركيز الايونات TH وTAC ) بين أن الماء الموجود عند خروجه من محطة المعالجة ذو نوعية جيدةSO4²-، وCL-، Mg²+ ، Ca²+ ، PO4ᶟ- ، NOᶟ-( للغاية من خلال مقارنة القيم المقاسة لكل عنصر مع مقاييس المياه الصالحة للشرب. الجانب الآخر الذي يهم هذه الدراسة هو التأثير المحتمل على الواد أساسا الذي يتلقى المياه المصرفة والبيئة بشكل عام. ----------------------------------------------------------------------------------------------------------------------------------------------------------------- L’objectif principal de ce travail est de déterminer la qualité d'eau traitée et d’évaluer la performance de la station de déminéralisation des eaux de forage, qui alimente la commune de Sidi- Fredj, par osmose inverse. L’étude a été effectuée par la réalisation des prélèvements des échantillons d’eau au niveau de cinq points de la filière de traitement. Le suivi de certains paramètres physico- chimiques (le pH, la conductivité électrique de l’eau, le TH, l e TAC et les concentrations en ions ( NO ᶟ - , PO4ᶟ - , Ca ² + , Mg ²+ , C L - , et SO 4- ) ) a montré que l'eau à la sortie de la station de traitement des eaux est de très bonne qualité en comparant les valeurs mesurées pour chaque paramètre aux normes de potabilité. L’autre aspect qui intéresse cette étude est l'impact que peuvent avoir les rejets liquides chargés de cette station principalement sur les oueds qui les reçoivent et sur l'environnement en général.